PRAKTIK GOVERNANCE PERBANKAN INDONESIA DITINJAU DARI ASPEK RISIKO - Erwin Harinurdin; Asti Setiawati; Wahyu Nofiantoro (Program Pendidikan Vokasi Universitas Indonesia, 2013)
ABSTRACT - Performance -based banking structures Indonesia does not have a normal life charactersbanking and still largely determined by the ideological and political policies of the government. Bankingrecovery by using a very protective manner, such as from the purchase of government bonds with limited ormargin lending and guaranteed withdrawal. Various indicators such as bank loan-deposit ratio ( LDR ) andthe structure of third-party funds that are still dominated by short-term funds such as checking and savingsshows that the bank has not been able to carry out its primary function in the economic system, intermediation.In the framework of the restructuring and recovery of the national banking industry, Bank Indonesia hastaken some of the policies that are considered necessary. Some of these policies include the implementation of theprinciples of risk management (according to Bassel Accor) and Know Your Customer principles. Overall, thepolicy is structured in parent programs are often known as the Indonesian Banking Architecture (API). APIis expected to be the blue print as well as a reference for the Indonesian banking industry structure that isconsidered ideal for BI.Determine the number of actors performing the banking system, such as regulators, supervisors,shareholders, directors, management, internal audit, external auditors, rating agencies and owners of customerfunds. The role of each differ according to the position, accountability mechanisms and social expectations. ButPraktik Governance Perbankan IndonesiaDitinjau dari Aspek RisikoErwin H, Asti S, Wahyu NVolume 1, Nomor 2, pp 1-142the articulation of good governance as a protrusion of the mission, capacity and relationships to be aprerequisite for growth and stability.The method used is descriptive qualitative approach. Based on the results of the study concluded that thepractice of governance in the Indonesian banking system has not been implemented optimally.Keywords: Keywords: Banks, Risk, Governance.